AB0958 Proposal for a juvenile systemic sclerosis response index (JSSCRI): result of the consensus meeting in hamburg. germany 11th of december 2016. (15th June 2017) - Foeldvari, I; Furst, DF; Anton, J; Baildem, E; Blakley, M; Constantin, T; Reis, P Costa; Curran, M; Cutolo, M; Denton, C; Fligelstone, K; Hinrichs, B; et al.
Abstract : Background: Juvenile Systemic Sclerosis (jSSc) is an orphan disease. There is increasing interest in testing novel therapies in the management of fibrotic diseases. Therefore, it is very important to develop a Response Index for jSSc (JSScRI) to distinguish effective therapies from placebo. In 2014 at the 1st JSScRI Consensus Meeting in Hamburg, following two rounds of a Delphi process, a proposal for domains and items for a JSScRI were made. In 2016, the 2nd JSScRI Consensus Meeting was held in Hamburg, Germany. Objectives: To conduct a Nominal Group Technique (NGT) and select potential core data set items that could change as outcome measures) that will be incorporated in the development of a JSScRI. Methods: Before the 2nd JSScRI Consensus Meeting, the items from the 1st JSScRI Consensus Meeting (2014) were scored via Email, in a Delphi by the participants of the current meeting. Participants included 14 experts in adult and juvenile SSc and a patient partner. During the subsequent face to face NGT meeting, moderated by DEF, and the items were scored anonymously by the participants after a nominal group discussion. The domains and items were scored regarding their importance for 1 year clinical trial from 1 (not relevant at all) to 9 (most relevant). A priori, it was agreed by the participants that the goal of the NGT was to exclude items that: 1. Are not feasible and 2. do not represent a changeable outcome measure even though they may represent the impact of disease on quality of life, vocational or recreational activity. Items with a median score of <4 in which greater than 1/3 of participants scored 1–3 [despite the item having a median score >3] were excluded. Results: Seventy-one items in 13 domains were scored. Six items were not scored as they were felt to not represent an outcome measure or were non-feasible and six items received a median score less then 4. Table 1 provides an example of the musculoskeletal domain with the median scores for different outcome measures. Conclusions: In a rigorous, NGT consensus meeting, some item reduction for the JSScRI was achieved. Items will be tested in a prospective way in the patients of the inception cohort of juvenile SSc (www.juvenile-scleroderma.com). Disclosure of Interest: None declared